TREND ANALYSIS OF BUDGET REALIZATION STATEMENTS VILLAGE FUND REVENUE IN VILLAGE JILATAN ALUR KEC. BATU AMPAR KAB. TANAH LAUT 2015-2019 - Novella Aruna; Mufrida Zein; Bella Puspita Rininda (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
ABSTRACT The budget realization report is part of the allocation of village funds which provides information on the realization of income, expenditure, transfers, surplus / deficit, financing and remaining less / more in the budget and will then be compared in a period to analyze income and expenditure for the next period. This study aims to analyze trends in the Village Fund Budget Realization Report in the village of Jilatan Alur Kec. Batu Ampar Kab. Tanah Laut and the factors causing the increase or decrease in income in the village. This research uses analytical method techniques, namely trend analysis and mean absolute percentage error (MAPE) analysis. Based on the results of the study, the village fund income and village fund allocation income have increased every year, while the revenue sharing from levies and taxes has decreased in 2016. With a value ability of 25% it is said to be feasible in village fund income, 11% is said to be good in revenue sharing. yields and tax retribution and 8.2% are said to be very good in the village fund allocation income. And it can be seen that the factors causing the increase or decrease in income are sourced from village funds, sharing of taxes and levies and allocating village funds. ABSTRAK Laporan realisasi anggaran merupakan bagian dari alokasi dana desa yang menyajikan informasi realisasi pendapatan, belanja, transfer, surplus/defisit, pembiayaan dan sisa kurang/lebih dalam anggaran dan kemudian akan dibandingkan dalam suatu periode untuk menganalisis pendapatan dan pengeluaran untuk periode berikutnya. Penelitian ini bertujuan untuk menganalisis trend pada Laporan Realisasi Anggaran pendapatan dana desa di desa Jilatan Alur Kec. Batu Ampar Kab. Tanah Laut dan faktor penyebab naik atau turunnya pendapatan di desa tersebut. Penelitian ini menggunakan teknik metode analisis yaitu analisis trend dan analisis mean absolute percentage error (MAPE). Berdasarkan hasil penelitian bahwa, pendapatan dana desa dan pendapatan alokasi dana desa mengalami peningkatkan disetiap tahunnya, sedangkan pendapatan bagi hasil retribusi dan pajak mengalami penurunan ditahun 2016. Dengan kemampuan nilai sebesar 25% dikatakan layak pada pendapatan dana desa, 11 % dikatakan baik pada pendapatan bagi hasil dan retribusi pajak dan 8,2% dikatakan sangat baik pada pendapatan alokasi dana desa. Serta dapat diketahui faktor penyebab kenaikan atau penurunan pendapatan yaitu bersumber dari dana desa, bagi hasil pajak dan retribusi dan alokasi dana desa.